Innovative Air-Transport Policy Formulation & Analysis Conducive to Economic Growth and Sustainability - Hamzaee, Reza G. (Archives of Business Research, 2017)
The intuitive concept of strong economic effects of aviation and air transport has been unexceptionally supported by the abundantly clear evidence. Hence, formulation of a dynamic and sustainable policy, based on massive evidence, is considered as mandatory. Innovative policies would internalize major components of the existing positive externalities to enhance the success, efficiency, and viability of the industry, which would be conducive to economic development. This study applies an inductive method: Some evidence and empirically measured economic effects would lead to the formulation of an integrative economic policy framework that can be applied accordingly in the future.